اسلامی تعلیمات کی روشنی میں قومی قیادت کے بحران کا حل: ایک تجزیاتی مطالعہ: Resolving the Crisis of National Leadership in the Light of Islamic Teachings: An Analytical Study - Rabia Ilyas; Dr. Sajid Mahmood (Al-Amīr Research Journal for Islamic Studies, 2025)
The SHARIAH brought by Prophet Muhammad (peace be upon him), his beautiful example, is a source of guidance for every era. The teaching of Prophet (Peace be upon him) contain comprehensive principle to solve the problem of humans in every era and to deal with the challenges of every era. HAZRAT Muhammad (peace be upon him) is unique not only in the history of Islam but also in the history of the world, despite being the ruler and head of the exemplary welfare state of Medina, The entire history of humanity is unable to describe the example of the unparalleled simplicity contentment, Simplicity was so much so that on one occasion HAZRAT UMER (RA) said “One day I came to the Prophet (peace be upon him) and he was resting in his room, He was resting on a simple mat made of palm barks the marks of which were visible on the body of the Prophet (peace be upon him) There were few things in the house , seeing all this , HAZRAT UMER (RA)was astonished and said , O Messenger of Allah, QUASAR and KISRA enjoy the world be engrossed in its luxury and despite being the Messenger of Allah you have a cloth and marks of a mat on your body, Upon hearing this from HAZRAT UMAR (RA) the Prophet (peace be upon him) said: ‘’O UMAR, don’t you like that them to enjoy the luxury and comfort of this world and we are the AKHIRAH. The beloved Prophet (peace be upon him) used to pray for himself: ’’O Allah, keep me alive in a state of poverty, and raise me from this world in a state of poverty, and raise me up with the poor on the Day of resurrection’’ In this Article, we will try to understand the principle in the light of SEERAT TAYYABA that are essential for the leader of any good nation, such as the leader’s justice and fairness , peace and order in the nation, good Administration, and Human rights. Keywords: Leadership; Shariah perspective; prophetic teachings.